2010
DOI: 10.2967/jnumed.109.070813
|View full text |Cite
|
Sign up to set email alerts
|

99mTc(CO)3(NTA): A 99mTc Renal Tracer with Pharmacokinetic Properties Comparable to Those of 131I-OIH in Healthy Volunteers

Abstract: Studies in rats showed that the pharmacokinetics of the tricarbonyl core radiopharmaceutical 99m Tc(CO) 3 -nitrilotriacetic acid, 99m Tc(CO) 3 (NTA), were essentially identical to those of 131 I ortho-iodohippuran ( 131 I-OIH), the clinical gold standard for the measurement of effective renal plasma flow. Our objective was to compare the pharmacokinetics of these 2 tracers in healthy volunteers. Methods: 99m Tc(CO) 3 (NTA) was prepared with commercially available NTA and a commercially available kit and isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 18 publications
4
51
0
1
Order By: Relevance
“…[38] This relationship of a decrease in the θ P with an increase in the M-N length is most evident (Tables 2 and 3) when the θ P of the other complexes in this study (all of which have very similar Re-N lengths) are compared with the θ P for [Re(CO) 3 (6,6Ј-Me 2 bipy){HNC(CH 3 )OCH 3 }]BF 4 , which has slightly longer Re-N lengths and the smallest θ P value (4.0°).…”
Section: Structural Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…[38] This relationship of a decrease in the θ P with an increase in the M-N length is most evident (Tables 2 and 3) when the θ P of the other complexes in this study (all of which have very similar Re-N lengths) are compared with the θ P for [Re(CO) 3 (6,6Ј-Me 2 bipy){HNC(CH 3 )OCH 3 }]BF 4 , which has slightly longer Re-N lengths and the smallest θ P value (4.0°).…”
Section: Structural Resultsmentioning
confidence: 70%
“…[34,39] For the alkyl acetimidate complexes, the Re-N bond lengths varied from 2.1706 (17) 4 , in which the Re-N bond lengths are about 2.21 Å (as discussed above).…”
Section: Structural Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the goals in the radiopharmaceutics of renal agents has been to closely mimic the most original compound. For example, recently Taylor et al have developed a new renal agent, 99m Tc(CO) 3 (NTA), which demonstrated pharmacokinetic properties and renogram parameters essentially identical to those of 131 I-OIH in healthy humans (27). The structural and functional similarity of 131 I-OIH to PAH made 131 I-OIH the imaging gold standard for tubular function assessment.…”
Section: Discussionmentioning
confidence: 99%